Biotechnological valorization of biodiesel-derived glycerol: Trials with the non-conventional yeasts Yarrowia lipolytica and Rhodosporidium sp - Sofia Sarantou; Nikolaos G. Stoforos; Ourania Kalantzi; Seraphim Papanikolaou (Carbon Resources Conversion, 2021)
Four non-conventional yeast strains belonging to the genera Yarrowia and Rhodosporidium were cultivated under nitrogen-limited conditions in shake flasks with biodiesel-derived glycerol employed as sole substrate. The strains R. toruloides DSM 4444 and Y. lipolytica ACA-DC 5033 displayed better performances and were further studied. At initial glycerol (Gly0) ≈ 50 g/L, the strain ACA-DC 5033 produced dry cell weight (DCW) ≈7.0 g/L, and also secondary extra-cellular metabolites as citric acid (CA) at ≈16 g/L and polyols (Pol) (mannitol, erythritol and arabitol) at ≈21 g/L. In double-media (besides nitrogen also Mg was limiting) for Gly0 ≈ 50 g/L, a shift towards CA production occurred (CAmax ≈ 33 g/L). The strain DSM 4444 at Gly0 ≈ 50 g/L produced DCW = 18.1 g/L containing lipids = 30.3% in DCW. In single nitrogen-limited media with Gly0 ≈ 90 g/L, the strain ACA-DC 5033 produced Pol ≈ 48 g/L and CA ≈ 20 g/L, while the strain DSM 4444 produced DCW = 27.3 g/L containing lipid = 54.5% w/w. At the late growth phases, metabolites were re-consumed. Balanced growth phase (trophophase) and phase of secondary metabolite synthesis (idiophase) were successfully simulated with the aid of a modified Velhlust-Aggelis model. Lipid extraction process was studied for these two strains by using two different extraction methods. Yeast lipids contained mostly oleic acid, constituting suitable precursors for the synthesis of 2nd generation biodiesel.